HSLA Steels 2015, Microalloying 2015 &Amp; Offshore Engineering Steels 2015 2015
DOI: 10.1002/9781119223399.ch30
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Processing of Structural Steels with Dilute Niobium Additions

Abstract: -i - AbstractIn this thesis, the influence of various dilute Nb additions (0.005-0.02 wt%) on austenite microstructure evolution along thermomechanical processing, in terms of austenite recrystallisation and grain growth, were investigated using steels with three carbon content levels.At the homogenisation temperature of 1250°C, all dilute Nb additions were dissolved in low carbon steels whereas the Nb dissolution limits for 0.4 wt% and 0.6 wt% C steels were 0.012 wt% and 0.08 wt%, respectively. Dilute Nb addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Reproduced with permission from Springer [46]. Owing to the competing effect of recrystallisation and austenite grain boundary pinning at the onset of deformation-induced NbC precipitation, partial recrystallisation occurs during hot deformation [9,53]. Hot torsion testing of C–Mn–Cr–Nb rail steel at BHP Melbourne Research Laboratories, Australia (Ref 23 in [9]) indicated that austenite recrystallisation becomes sluggish during deformations at 1000C starting from 0.015–0.035 wt-% Nb, dissolved in 0.4–0.8 wt-% C steels reheated at 1260–1300C.…”
Section: Effect Of Niobium On Prior Austenite Grain Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from Springer [46]. Owing to the competing effect of recrystallisation and austenite grain boundary pinning at the onset of deformation-induced NbC precipitation, partial recrystallisation occurs during hot deformation [9,53]. Hot torsion testing of C–Mn–Cr–Nb rail steel at BHP Melbourne Research Laboratories, Australia (Ref 23 in [9]) indicated that austenite recrystallisation becomes sluggish during deformations at 1000C starting from 0.015–0.035 wt-% Nb, dissolved in 0.4–0.8 wt-% C steels reheated at 1260–1300C.…”
Section: Effect Of Niobium On Prior Austenite Grain Structurementioning
confidence: 99%
“…It was suggested to confine the rolling to C to minimise these problems. More recently, Cui et al [53] also showed partial recrystallisation of hot deformed austenite at finish deformation temperatures of 950–1000C for 0.6C–0.018Nb (wt-%) steel.…”
Section: Effect Of Niobium On Prior Austenite Grain Structurementioning
confidence: 99%